Performance analysis of an SMA negative-stiffness double-concave friction pendulum bearing in reinforced concrete frame structure - Shipeng Feng; Ziquan Yang; Liang Wang; Shanchun Fu; Jun Peng; Pengfei Li; Hang Zhao (Soil Dynamics and Earthquake Engineering, 2026)

Agaricus bisporus polysaccharides alleviate high-fat diet-induced cognitive impairment via microbiota-gut-brain axis modulation - Chujing Fu; Kai Ye; Zhichang Qiu; Xinyu Hu; Xiaoxuan Wang; Hang Xiao (Food Research International, 2026)

Study on the size effect model of mode I fracture characteristics in Longmaxi formation shale based on DIC and acoustic emission technology - Yu Suo; Xian-hang Wei; Gui-quan Wang; Cui-long Kong; Guang-chao Zhang; Xi Chen; Xiaofei Fu; Zhe-jun Pan; Bin Huang (Soil Dynamics and Earthquake Engineering, 2026)

Two-stage synergistic flocculation based on chitosan/sodium hyaluronate polyelectrolyte complexes for rapid underwater visual clarification in turbid environments - Jiawei Fu; Junjie Li; Hang Xu (Journal of Water Process Engineering, 2026)

Glacial fluctuations over the past two millennia on the arid northeastern Tibetan Plateau - Weicheng Wang; Jie Wang; Haopeng Geng; Hang Cui; Jinkun Qiu; Zihan Fu (Global and Planetary Change, 2026)

A fractional creep prediction model for rock based on isochronous stress-strain curve characteristics and its finite difference implementation - Juntao Yang; Yanqi Song; Chuanpeng Liu; Hang Fu; Zhibin Hao; Yuhua Zhang; Xiaohan Li (Computers and Geotechnics, 2026)

Two-dimensional metal-organic frameworks: Structural design, electron/ion transport, and energy-storage applications - Yiming Wu; Ruiying Fu; Zhishu Zheng; Xutian Yang; Hang Zhan; Hua Wu; Kuaibing Wang; Ping Yang (Chemical Engineering Journal, 2026)

EXtreme Gradient Boosting for Lithology Identification with Well Logs: A Case Study from the Salt Lake Area, Eastern Qaidam Basin, China - Zhong-yi Duan; Fu-long Zheng; Hang-yu Yue; Jia-pan Yan; Kun Xiao; Ting-yan Zhang; Jia-dong Yan (Applied Geophysics, 2026)

Methanol vehicles with low PN23 emissions may still exhibit a potential SubPN23 particle burden - Jie Yao; Xinping Yang; Yitu Lai; Wanyou Luo; Hongfei Chen; Yunjing Wang; Xin Li; Mingliang Fu; Hang Yin; Yan Ding (Journal of Cleaner Production, 2026)

Ionic liquids and SWCNT synergistically construct a dual-transport network in PEDOT: PSS composite fibers for supercapacitor electrodes - Yuxin Fu; Xiuchen Wang; Gege Hang; Yanan Wang; Zhe Liu (Chemical Engineering Journal, 2026)

From bacterial template to green catalyst: Bio-fabrication of nanostructured nickel hydroxycarbonate for oxygen evolution via microbial mineralization - Feng Duan; Qichang Li; Li Xu; Haifang Wu; Ercai Pan; Wei Ding; Junhui Guo; Hang Ping; Liuyi Zhao; Hao Xie; Zhengyi Fu; Zhaoyong Zou (Chemical Engineering Journal, 2026)

Hyperoside-based self-assembled hydrogel for modulating osteoimmune microenvironment to combat bacterial infections and facilitate bone repair - Xiang Gao; Xiaojing Zhang; Hang Liu; Xinwei Fu; Tao Zhang; Xiao Liang; Yifan Ren; Xingyu Yang; Xinliang Peng; Liqun Xu; Prasathkumar Murugan; Yuejun Kang; et al. (Chemical Engineering Journal, 2026)

Retraction notice to “Light absorption of black carbon and brown carbon in winter in North China Plain: comparisons between urban and rural sites” [Sci. Total Environ. 770 (2021) 144821] - Jiaxing Sun; Conghui Xie; Weiqi Xu; Chun Chen; Nan Ma; Wanyun Xu; Lu Lei; Zhijie Li; Yao He; Yanmei Qiu; Qingqing Wang; Xiaole Pan; et al. (Science of The Total Environment, 2026)

Retraction notice to “High daytime abundance of primary organic aerosols over Mt. Emei, Southwest China in summer” [Sci. Total Environ. 703 (2020) 134475] - Yue Zhao; Hong Ren; Junjun Deng; Linjie Li; Wei Hu; Lujie Ren; Siyao Yue; Yanbing Fan; Libin Wu; Jie Li; Yele Sun; Zifa Wang; et al. (Science of The Total Environment, 2026)

Retraction notice to “Influence of the morphological change in natural Asian dust during transport: A modeling study for a typical dust event over northern China” [Sci. Total Environ. 739 (2020) 139791] - Yu Tian; Zhe Wang; Xiaole Pan; Jie Li; Ting Yang; Dawei Wang; Xiaoyong Liu; Hang Liu; Yuting Zhang; Shandong Lei; Yele Sun; Pingqing Fu; et al. (Science of The Total Environment, 2026)

Discovery of isotope 153Hf near the proton drip line via isochronous mass spectrometry: extending the nuclear landscape with HIAF - Hongfu Li; Min Zhang; Hongyang Jiao; Xing Xu; Chaoyi Fu; Jinyang Shi; Jiahao Lv; Xu Zhou; Yuanming Xing; Mingze Sun; Yuhu Zhang; Xiaohong Zhou; et al. (Science Bulletin, 2026)

LNP-mRNA-engineered fibroblasts delivering TNF-α antibodies alleviate intervertebral disc degeneration by modulating the inflammatory microenvironment - Jianan Chen; Tong Xing; Jialei Song; Hang Zhang; Shaotian Fu; Lizhi Jiang; Yiqi Xu; Lei He; Huatao Liu; Hailong Ma; Xin Wang; Tangjun Zhou; et al. (Chemical Engineering Journal, 2026)

Bionic Tursiops Truncatus-inspired dual-mode sensor for proximity sensing and high-resolution tactile perception - Hang Yu; Zhao Xu; Haowen Chen; Guangchao Wang; Qiang Sun; Haoran Fu; Huaping Wu; Aiping Liu (Chemical Engineering Journal, 2026)

Cisplatin-induced renal injury: ROS-mediated oxidative stress — mechanism and antioxidant intervention strategies - Zhiwei Huang; Linpeng Yang; Yupeng Chu; Hang Yu; Xiaoyan Fu; Meifang Liu; Xianhong Du; Liyuan Wang; Hongxia Zhang (Chemico-Biological Interactions, 2026)

Characteristics and source analysis of fluorescent aerosol particles at a typical rural site in the North China Plain during autumn and winter - Yang Zhou; Wei Hu; Siyao Yue; Wanyun Xu; Rui Jin; Boran Hua; Zihe Li; Libin Wu; Junjun Deng; Jiangchuan Tao; Nan Ma; Hang Su; et al. (Atmospheric Environment, 2026)

The Single Amino Acid Substitution in WcaJ(Ser332Leu) Promotes Hypervirulent Klebsiella Pneumoniae Resistant to Bacteriophage and Virulence Attenuated - Lingrui Shi; Zhen Li; Li Xiang; Shiqi Tang; Hang Lai; Jiang Wu; Yingshun Zhou; Li Fu (Probiotics and Antimicrobial Proteins, 2026)

From economic crop to high-value product: Fermentation of chestnut protein by Lactobacillus rhamnosus ameliorates chronic inflammation via the gut microbiota–SCFAs axis - Dongze Qin; Wenhui Fu; Haoxin Cui; Haiwei Liu; Hang Yang; Yaozhong Hu; Ruican Wang; Xuemeng Ji; Shuo Wang (International Journal of Food Microbiology, 2026)

Polystyrene nanoplastics disrupt iron homeostasis by promoting FPN1 ubiquitination in GC-2spd(ts) cells - Xinru Cui; Yitong Shang; Liyang Ding; Zhen Zhang; Yu Deng; Tengjiao He; Bo Xu; Xufeng Fu; Xing Du; Hang Han (Toxicology, 2026)

Heat-induced methylglyoxal impairs plant thermotolerance by repressing cpHSC70-1-mediated chloroplast protein import via post-translational modification - Feng Ding; Yue-Xin Liu; Shi-Hang Fan; Wei Hua; Ying-Tang Lu; Zheng-Wei Fu (Molecular Plant, 2026)

Multifaceted biocontrol mechanisms of Bacillus amyloliquefaciens F028 against Botrytis cinerea in postharvest tomato fruit - Fu-Lai Han; Jin-Xiu Zhao; Ming-Yi Wang; Meng-Fei Li; Zhe Zhang; Xiao-Hang Cui; Yu-Fei Li; Hao-Jie Jiang; Qing-Xue Jiao; Jie Yang; Xin Liu; Guang-Chao Liu (International Journal of Food Microbiology, 2026)

Non-uniform gradient depressurization strategy for balancing heat transfer and gas production in Dual-Gas Co-Production systems - Xian Sun; Hang Zheng; Hui Yang; Fu-Jun Cheng; Zhen Pan; Wen-Chen Han; Hao-Xiang Sun; Yang Yu; Ling-Ban Wang; Chang-Yu Sun (Fuel, 2026)

Cyclophosphamide-induced iron homeostasis imbalance triggers ovarian toxicity through ferroptosis of ovarian granulosa cells in a mitophagy crosstalk manner - Bo Xu; Xiaoqiang Luo; Tengjiao He; Yu Deng; Yitong Shang; Hang Han; Xufeng Fu (Chemico-Biological Interactions, 2026)

A review on the effects of iron (Fe) on Ulva prolifera: Mechanisms of growth promotion, inhibition, and biochemical responses - Md Mohidul Islam; Sahr Lamin Sumana; Mukhtar Abdullateef Muhammad; Gelena Urgesa Ayana; Shisi Fu; Abubakar Shuaibu; Ahmed E. Elshafey; Yifei Shen; Yuqing Sun; Md. Simul Bhuyan; Md. Enamul Hoq; Touhidul Hoque Shuvo; et al. (Algal Research, 2026)

Species-specific accumulation and biomagnification of PFASs in aquatic and terrestrial organisms from the Xisha Islands - Yu-Quan Zhang; Jun Xiang; Jiao-feng Gu; Peng Zeng; Qi-Fei Peng; Yong-Fu Chen; Yu-Feng Hu; Li-cheng Wang; Hang Zhou; Ling Mo (Marine Pollution Bulletin, 2026)

Molecular insights into the coupled transformation of dissolved organic matter and arsenic in lake sediment driven by algal input under redox fluctuations - Yuanhang Li; Zhaoying Shen; Shaokang Zhang; Hang Fu; Yuheng Sun; Shoujuan Tang; Hong Huang; Lei Shi (Water Research, 2026)

Natural and anthropogenic controls on rare earth elements in groundwater: Indicative significance for distinguishing agricultural and urban-industrial impacts - Hang Meng; Guangcai Wang; Fu Liao; Hairu Mao; Bo Li; Fengxia Liu; Xianglong Chen; Hongyu Zhang; Zhiyuan Qiao (Journal of Hazardous Materials, 2026)

A novel model to assess the hydrogen storage capacity in depleted gas reservoirs considering dynamic geo-bio-chemical reactions - Guicheng Jing; Yalong Li; Hang Zhao; Zhangxing Chen; Jingang Fu (Journal of Cleaner Production, 2026)

Ultrasound-activated in situ nano-vaccines (SATNAV) for precise CRPC sono-immunotherapy via multi-reprograming the immunosuppressive microenvironment - Xinzhi Xu; Jing Fu; Yujie Wan; Jiaqi Gong; Ruixia Hong; Jia Tang; Qizhi Wang; Ying Li; Kaifeng Huang; Yizhe Zhong; Hang Zhou; Jichun Yang; et al. (Chemical Engineering Journal, 2026)

An ultra-sensitive and selective Janus CrSiGeN4-based sensor for ppb-level NO detection with robust oxidation and humidity resistance - Shen-Ao Gao; Hang He; Chuan-Kui Wang; Xiao-Xiao Fu (Chemical Engineering Journal, 2026)

Biomechanical changes in gait before and after fatigue in unilateral transtibial amputees - Xinyu Fu; Zihan Song; Shousheng Zhang; Zhouqing Xu; Xinming Wu; Wei Tang; Hang Xu (European Journal of Applied Physiology, 2026)

Palladium recovery from wastewater using electric field-enhanced ultrafiltration assisted with polyethyleneimine and electro-decomplexation/electrodeposition - Hang Yin; Wenwu Li; Shuhuai Shen; Saina Zheng; Dafang Fu; Jianglei Xiong; Ming Chen (Journal of Cleaner Production, 2026)

Synergistic removal of tetracycline and cadmium in real wastewater using KHCO3-Modified biochar derived from agricultural waste: Mechanism and engineering application - Yuzheng Zou; Wentao Yang; Tianling Fu; Yonglin Chen; Shiyu Yang; Bing Wang; Jian Zhang; Hang Zhou; Liyu Yang; Pan Wu (Journal of Environmental Management, 2026)

Interface engineering of Si/graphene composites via compression-assisted fast joule heating for enhanced Lithium-ion battery anodes - Pengcheng Deng; Hang He; Tingting Yi; Junfeng Pan; Wenjie Liang; Beibei Yu; Zeman Xie; Zhijun Li; Danish Khan; Zeguo Tang; Xiao Yu; Dongjv Fu; et al. (Chemical Engineering Journal, 2026)

Design and synthesis of novel fucosylated chondroitin sulfate derivatives as intrinsic FXase inhibitors and evaluation of their antithrombotic activities - Dongliang Xu; Xi Gong; Lisha Lin; Hang Dong; Yijian Wen; Yingnian Li; Gang Fu; Yuanhang Ma; Weicheng Xiong; Tianyu Guan; Ao Sun; Xiangbao Meng; et al. (Carbohydrate Polymers, 2026)

Spatial evolution and driving factors of surface water chemistry in the Duliujiang River Basin, Southwest China - Zhiyong He; Hang Li; Zengping Ning; Jinshuai Fu; Yanqiong Luo; Qianchen Liu; Wenjia Lu; Yizhang Liu; Jing Sun; Chengshuai Liu (Acta Geochimica, 2026)

Perspectives on two major bioactives in ginger, 6-gingerol and 6-shogaol, focusing on the in vivo metabolic fate and bioactivities - Yu Zhou; Jinkai Zheng; Zhenjun Zhu; Peiyi Shen; Hengjun Du; Chujing Fu; Kai Ye; Mingyue Song; Yong Cao; Hang Xiao (Critical Reviews in Food Science and Nutrition, 2026)

Catalysis-inspired d-band center engineering enables hydrogen-suppressed zinc anodes for long-life aqueous zinc-ion batteries - Chunhui Gao; Zhenjing Jiang; Jie Chen; Kaining Zhang; Huijun Yang; Ruwei Chen; Hang Yang; Qingjin Fu; Zheng Li; Nana Xu; Mengran Wang; Bo Hong; et al. (Science Bulletin, 2026)

Corrigendum to “Straw return enhances nitrogen loss from groundwater in agricultural areas by triggering the switch from DNRA to denitrification”. [J. Hydrol. 662 (2025) 133818] - Han Wu; Linna Jia; Zhiyuan Zhang; Hang Fu; Rucai Ma; Jia Xin (Journal of Hydrology, 2026)

MOF-derived AgCl/ZnO heterojunction photocatalysts: Enhanced degradation of tetracycline via promoted charge carrier separation - Kailai Zhang; Ao Feng; Chuwen Ou; Qinwu Wu; Zhen Meng; Hang Chen; Shurui Xu; Xiaobo Fu; Wenbo Liao; Baizeng Fang; Guoyu Zhong (Environmental Research, 2026)

One-step therapy strategy: Multifunctional chitosan-based hydrogel enriched with platelet-rich plasma for enhanced healing of infected wounds - Han Zhang; Hang Wu; Xianchun Fu; Lun Liu; Yuan Fang; Yongtao Zhang; Tianrui Wang; Yingze Zhang; Liang Liu (Carbohydrate Polymers, 2026)

Mitochondrial ORF188 confers salt stress tolerance in rapeseed via an ATP-dependent enhancement of antioxidant capacity - Shi-Hang Fan; Zi-Hong Huang; Jun Li; Xiang Ji; Wei Hua; Zheng-Wei Fu (Plant Cell Reports, 2026)

Eliminating Microcystis aeruginosa and secondary pollutants via photo-Fenton process over Iron-MOF - Hong- Yu Chu; Zheng-Xing Liu; Jian-Feng Wang; Xuchun Qiu; Fu-Xue Wang; Shao-Long Chen; Hui-Min Yu; Fei Wang; Guang-Chi Liu; Ruo-Xuan Mei; Xin-Jie Li; Xiao-Hang Xu; et al. (Water Research, 2026)

Multiscale insights of interfacial transport and kinetics in acidic CO2 electroreduction - Hang Wang; Yang Wang; Jian Wang; Zhaojian Liang; Long Ma; Chuanjun Wang; Xun Zhu; Jun Li; Qian Fu; Qiang Liao (Science Bulletin, 2026)

Economic benefits of carbon source selection for polyphosphate-accumulating organisms in enhanced biological phosphorus removal - Jing Yuan; Liping Chen; Xiaojing Xie; Hang Chen; Xiaodong Du; Acong Chen; Haixin Zheng; Fu Huang; Sijia Ji; Zemin Li; Xianghui Liu; Zhiyi Deng; et al. (Environmental Research, 2026)

Geochemical signatures of mud and core gases from the Milun Fault Scientific Drilling (MiDAS), Taiwan: Implications for fluid pathways and crustal degassing - Ching-Chou Fu; Kuo-Hang Chen; Kuo-Wei Wu; Pei-Ling Wang; Ai-Ti Chen; Vivek Walia; Kuo-Fong Ma (Chemical Geology, 2026)

Straw return enhances nitrogen loss from groundwater in agricultural areas by triggering the switch from DNRA to denitrification - Han Wu; Linna Jia; Zhiyuan Zhang; Hang Fu; Rucai Ma; Jia Xin (Journal of Hydrology, 2025)

Formaldehyde emissions from light-duty gasoline vehicles: Emission characteristics and future trends - Junchao Zhao; Xinping Yang; Zhining Zhang; Mingliang Fu; Yunjing Wang; Songdi Liao; Zhipeng Tu; Lijuan Qi; Xiaotong Wang; Zhenyu Luo; Hang Yin; Yan Ding (Journal of Hazardous Materials, 2025)

High-performance and fast fiber-optic SPR gas sensor based on WO3/SnO2 nanocomposites films for room-temperature NH3 detection - Chong Li; Yan Wang; Jinqiao Hou; Huanming Wang; Jingting Luo; Chen Fu; Fujian Ren; Jikai Zhang; Huiling Ong; Chenze Lu; Hang Xiao; Xi Chen; et al. (Journal of Environmental Chemical Engineering, 2025)

Interfacial water layer modulation for efficient photocatalytic CO2 reduction - Jingyi Pang; Hang Zhou; Zejiang Huang; Xiaomeng You; Beibei Xu; Xiaobin Fu; Yilong Weng; Xue-Lu Wang; Ye-Feng Yao (Chemical Engineering Journal, 2025)

A Fractional Full-Stage Creep Prediction Model for Salt Rock Based on Stress Threshold and Damage Evolution - Juntao Yang; Yanqi Song; Zhibin Hao; Zhixin Shao; Junjie Zheng; Chuanpeng Liu; Hang Fu (Rock Mechanics and Rock Engineering, 2025)

Transcriptomic profiling reveals mechanism, therapeutic potential, and prognostic value of cancer stemness characteristic in nasopharyngeal carcinoma - Jin-Wei Chen; Run-Nan Shen; Jiang-Quan Zhu; Ying-Hang Wang; Liang-Min Fu; Yu-Hang Chen; Jia-Zheng Cao; Jin-Huan Wei; Jun-Hang Luo; Jia-Ying Li; Cheng-Peng Gui (Functional & Integrative Genomics, 2025)

Emerging Teleconnected Patterns Enhance Predictability of East Asian Summer Extremes - Wen Zhou; Zheng-Hang Fu; Ruhua Zhang (Journal of Meteorological Research, 2025)

On-off-on electrochemiluminescence biosensor with dual-cycle amplification for ultrasensitive prenatal detection of thalassemia mutations using lanthanide europium nanorods - Ya-Qian Xie; Ya-Shu Wei; Hang Du; Yu-Yi Zhou; Lin-Yi Liu; Fu-Cun Wei; Yan-Ni Luo; Xue-Cai Tan; Ke-Jing Huang; De-Fen Feng (Analytica Chimica Acta, 2025)

Structure characterization, simulated digestion, and microbial modulation of Pleurotus ostreatus polysaccharides - Kai Ye; Chujing Fu; Hengjun Du; Shiguo Chen; Donghong Liu; Gaoxing Ma; Hang Xiao (Food Chemistry, 2025)

Suppression of Fe loss to promote reconstructed surface via black phosphorus over NiFeB nanosheets for efficient water oxidation - Zehao Wang; Huayu Chen; Yesheng Fu; Hang Yin; Dandan Yu; Junhui Liang; Yuexiang Huang; Liuqi Wang; Wei Gao; Da Chen; Yang Hou (Chemical Engineering Journal, 2025)

Androgen induces 3′UTR shortening of de novo lipogenesis genes by alternative polyadenylation in prostate cancer cells - Wei-Jie Sun; Fei Liang; Hui Zhao; Yun-Mei Wang; Zhong-Yin Zhou; Hui Xu; Hang Liu; Dong Tang; An-Long Xu; Yong-Gui Fu; Xi Li; Jun Ouyang; et al. (Science China Life Sciences, 2025)
Alternative polyadenylation (APA) is a pervasive mechanism that is emerging as a formidable player in post-transcriptional regulation. The transcriptional landscape can be altered via APA in response to various stimulating factors. Using the PacBio single-molecule long-read sequencing method, we present for the first time the 3′UTR landscape and reveal a global increase of APA events in prostate cancer (PCa) LNCaP cells in response to androgen dihydrotestosterone (DHT), a critical regulator of PCa progression. With evidence from differential gene expression analyses of Illumina RNA-sequencing data, we demonstrated that genes with DHT-induced changes in both expression and APA were enriched in lipid metabolism. These genes predominantly supported de novo fatty acid synthesis, such as FASN and ACSL3 . Furthermore, we showed that an isoform switch to the proximal poly(A) site of these genes depended on the androgen receptor, and the expression of cancer-associated genes was upregulated by the escape of miRNA-regulated repression machinery. To address the role of key gene shortening in PCa, we prepared 22RV1-FS cells missing the distal poly(A) signal of FASN in the AR + PCa cell line 22RV1 using CRISPR/Cas9 technology. As expected, the edited 22RV1-FS cells overexpressed FASN mRNA and protein and were inclined to cell proliferation in vitro and tumorigenesis in vivo . Interestingly, we found that FASN transcripts with a shortened 3′UTR were significantly increased in advanced PCa and castration-resistant prostate cancer compared with benign prostate hyperplasia, suggesting a possible association between usage of the proximal poly(A) site and disease progression. Therefore, our study highlights the importance of the APA mechanism in response to DHT stimulation in PCa cells and provides a novel regulatory mechanism through which DHT-induced APA causes altered expression of de novo lipogenesis genes, with a possible association with the progression of PCa.

Inhibition of the NLR pathway alleviates MAPK1 mutation-driven proliferation and differentiation deficits and enhanced apoptosis in P19 cells - Tingying Lei; Lei Liu; Fei Guo; Ru Li; Li Zhen; Fang Fu; Min Pan; Jin Han; Hang Zhou; Chunling Ma; Ruibin Huang; Xinyi Zhao; et al. (Tissue and Cell, 2025)

Separation of Co and Li from spent lithium-ion battery leachate using a synergistic extraction system based on Cyanex 272 and Cyphos IL 101 - Ze-Hang Chen; Lei Xu; Chen Chen; Zong-Bin Lv; Ming-Lai Fu; Baoling Yuan (Journal of Environmental Chemical Engineering, 2025)

The negative regulated immune mechanism of Skp1-Cullin1-F-box (SCF) E3 ubiquitin ligase-mediated HOS15-dependent responses in banana - Xinyi Chen; Xingchen Jia; Ruizhou Fu; Maoli Wang; Hang Rong; Jinyi Wei; Zishu Wang; Mingyuan Wang (Plant Cell Reports, 2025)

Genetic burden and multidimensional predictors in prenatal diagnosis of fetal congenital diaphragmatic hernia - Ruibin Huang; Fang Fu; Shanshan Mei; Liyuan Liu; Wei Zhong; Jin Han; Qiuxia Yu; Hang Zhou; Chunling Ma; Li Zhen; Min Pan; Qiong Deng; et al. (Human Genetics, 2025)

Scaling of urban residential building stock system and carbon emissions accounting for vacant houses in China - Wanru Leng; Guangxin Liu; Xiaoyu Cheng; Yang Li; Shoujuan Tang; Jun Ning; Yuanhang Li; Hang Fu; Lei Shi (Resources, Conservation and Recycling, 2025)

Bisphenol A caused abnormal spermatogenesis of Eriocheir sinensis through es-ERR/es-KIF4A pathway with discussion of BPA substitutes - Yu Yang; Di Wu; Tian Lei; Hang-Yuan Zhao; Jun-Jie Yu; Lan-Min Wang; Ding-Xi Liu; Yan-Shuang Zhao; Jia-Hao Ni; Fu-Qing Tan; Wan-Xi Yang (Journal of Hazardous Materials, 2025)

CO2 electroreduction in acidic zero-gap electrolyzers: A modeling-based quantitative assessment of electrochemical and energy characteristics - Yang Wang; Hang Wang; Zhongyin Kang; Zhisheng Long; Guifeng Zhou; Qian Fu; Xun Zhu; Qiang Liao (Chemical Engineering Journal, 2025)

Alkyl chain engineering in β-linked dimer acceptors: Balancing crystallinity and phase separation for high-performance organic photovoltaics - Yun Li; Jiawei Fu; Hang Jiang; Zhongwei Ge; Haisheng Ma; Yinuo Yang; Xiaobo Sun; Shouchun Yin (Chemical Engineering Journal, 2025)

Inversion of Rayleigh wave dispersion curves based on the Osprey Optimization Algorithm - Zhi Li; Hang-yu Yue; De-xi Ma; Yu Fu; Jing-yang Ni; Jin-jun Pi (Applied Geophysics, 2025)

Mass spectrometry imaging unveils the fate of azithromycin in zebrafish: Uptake, distribution, transformation, and metabolic impact - Hang Fu; Leiyi Ji; Yanxiao Jiang; Changjun Yu; Hong Zhang; Guangfeng Kan; Jie Jiang (Journal of Environmental Chemical Engineering, 2025)

Two new megastigmane glycosides from the leaves of Nicotiana tabacum and their anti-inflammatory activities - Peng-fei Yang; Wei Wu; Hang-hang Han; Qing-fu Wang; Lei Li; Ze-ning Wang; Duo-bin Mao; Zhi-fei Chen (Natural Product Research, 2025)

Decoding EGFR A289 Mutation in Glioblastoma: A Predictive Biomarker Framework and Targeted Therapeutic Insights - Xiaoxue Zhu; Haitao Fu; Xuejing Li; Hang Zhou; Zekai Li; Luyang Xie; Guilin Li (Journal of Molecular Neuroscience, 2025)

In vitro digestion and fermentation characteristics of Agrocybe cylindracea polysaccharides and their interaction with the gut microbiota - Chujing Fu; Kai Ye; Zhichang Qiu; Gaoxing Ma; Shiguo Chen; Hang Xiao (Food Research International, 2025)

Curcumin-loaded proliposomes via glycerol-infused: Mechanism, stability and antioxidant activities - Hang Xu; Dongwen Fu; Yunong Zhang; Huihui Wang; Wentao Su; Yukun Song; Mingqian Tan (Food Chemistry, 2025)

Vertical distribution and seasonal variations of dicarboxylic acids in urban PM2.5: Insights from multi-level observations on 600 m Canton tower in Guangzhou - Dian Ye; Shengzhen Zhou; Yuxuan Liang; Chunlei Cheng; Chenglei Pei; Yao Li; Min Gao; Xijing Sun; Siqi Chen; Jian Hang; Pingqing Fu; Shaojia Fan (Atmospheric Environment, 2025)

Mass deposition of microbes from wildfire smoke to the sea surface microlayer - Siyao Yue; Yafang Cheng; Lishan Zheng; Senchao Lai; Shan Wang; Tianli Song; Linjie Li; Ping Li; Jialei Zhu; Meng Li; Lianfang Wei; Chaoqun Ma; et al. (Limnology and Oceanography, 2025)
Microbes in the sea surface microlayer (SML) are key to connecting the ocean and the atmosphere, affecting the exchange of matter, momentum, and heat at the interface. However, their sources have never been quantified systematically. Seawater has long been deemed their major source, whereas atmospheric deposition is regarded as trivial or merely providing additional nutrients. Here, combining atmospheric observations and quantitative budget analyses, we show that during the Indonesian peatland wildfire events the smoke can directly deposit abundant microbes into the SML, which can be comparable to the estimated supply from seawater and potentially diversify the microbial community of the SML. This land–air–ocean interaction is relevant for global climate, as it may induce previously unknown effects on the air–sea interactions, especially in an increasingly warming future with more intensifying wildfires.

Identifying the flows and stocks of additives in polyvinyl chloride plastics for balancing environmental and economic impacts - Kai Zhao; Zhenye Zhang; Yijun Li; Hang Fu; Xiting Peng; Ran Tao; Zhiyuan Li; Weigu Wen; Xin Xie; Shanying Hu (Resources, Conservation and Recycling, 2025)

Effects of ferrite porous confined biochar nanoreactor on the adsorption and desorption of Pb and Cd - Ning Liu; Rongxin Zhou; Shuangxue Huang; Jiming Zhang; Hongda Zhang; Hang Liu; Xiao Du; Dongyi Zhang; Renlong Zhang; Zhentao Sun; Shifeng Fu; Xiumei Zhan (Journal of Water Process Engineering, 2025)

Selective recovery of lithium from spent LiFePO4 batteries based on PMS advanced oxidation process - Zong-Bin Lv; Lei Xu; Chen Chen; Ze-Hang Chen; Ming-Lai Fu; Baoling Yuan (Journal of Environmental Chemical Engineering, 2025)

Photocatalytic degradation of xanthate by S–scheme CeO2/g–C3N4 heterojunction and its DFT calculation - Deqin Meng; Li Wang; Cheng Zhong; Jiani Fu; Xiaolong Hu; Dengzheng Gao; Qingbin Guo; Jinbo Hou; Hang Zhao (Journal of Water Process Engineering, 2025)

Lactobacillus paracasei GF027 promotes growth and cognitive development in juvenile rats via regulating intestinal microecology and nourishing the brain - Hang Yang; Yuanyifei Wang; Haiwei Liu; Jin Wang; Dancai Fan; Yi Sun; Huan Lv; Wenhui Fu; Shuo Wang (Food Bioscience, 2025)

Broad-spectrum anti-inflammatory and antioxidant therapy of inflammatory-storm actuated diseases via programmable self-derived cryo-dead neutrophils - Bin Li; Qiuxia Gao; Yunxia Wu; Hongyi Lei; Shengchao Ma; Wei Wang; Hang Sun; Weifeng Ma; Judun Zheng; Chenchen Yuan; Yunlong Zhang; Yue Jia; et al. (Chemical Engineering Journal, 2025)

Achieving 18.29% efficiency of layer-by-layer all polymer solar cells enabled by iridium complex as energy donor and crystallizing agent - Yuheng Ni; Jiayu Li; Miao Zhang; Hongyue Tian; Hang Zhou; Lu Zhang; Wenjing Xu; Guorui Fu; Xingqiang Lü; Sang Young Jeong; Wai-Yeung Wong; Han Young Woo; et al. (Chemical Engineering Journal, 2025)

Effects of dietary resveratrol supplementation on the growth performance, physiological health, transcriptomic response, and intestinal microflora of Litopenaeus vannamei - Zhibin Fu; Jian Chen; Hang Yuan; Yudong Zheng; Gongyu Li; Sheng Ke; Shuang Zhang; Lili Shi (Aquaculture, 2025)

Dynamic analysis of intrahepatic T cells reveals a unique group of restorative Cxcr3+ tissue-resident CD4 T cells in acute liver injury - Shen-Xi Ouyang; Yong-Gang Xu; Peng Ding; Yue Long; Zhen Zhang; Si-Jia Sun; Yan Zhang; Hang Yin; Jia-Bao Zhang; Qi Cao; Fu-Ming Shen; Pei Wang; et al. (Toxicology, 2025)

Emission control status and future perspectives of diesel trucks in China - Shihai Zhang; Mingliang Fu; Hefeng Zhang; Hang Yin; Yan Ding (Journal of Environmental Sciences, 2025)

Immobilization or mobilization of heavy metal(loid)s in lake sediment-water interface: Roles of coupled transformation between iron (oxyhydr)oxides and natural organic matter - Yuanhang Li; Shaokang Zhang; Hang Fu; Yuheng Sun; Shoujuan Tang; Jinwen Xu; Jun Li; Xiaofeng Gong; Lei Shi (Science of The Total Environment, 2025)

Application of multi-angle spaceborne observations in characterizing the long-term particulate organic carbon pollution in China - Yun Hang; Qiang Pu; Qiao Zhu; Xia Meng; Zhihao Jin; Fengchao Liang; Hezhong Tian; Tiantian Li; Tijian Wang; Junji Cao; Qingyan Fu; Sagnik Dey; et al. (Science of The Total Environment, 2025)

Comprehensive susceptibility assessment of continental glacier ice avalanches: a case study of glaciers on the northwestern Tibetan Plateau - Yuqi Shang; Hao Sun; Gaojian Miao; Chao Wang; Jinfeng Liu; Wentao Zhang; Huaquan Yang; Hang Fu (Landslides, 2025)

Combined effect of polystyrene nanoparticles and chlorpyrifos to Daphnia magna - Yu-Hang Zhang; Rong-Yao Gao; Few Zhu; Li-Min Fu; Jian-Ping Zhang (Chemosphere, 2024)

Candidatus Thiothrix phosphatis SCUT-1: A novel polyphosphate-accumulating organism abundant in the enhanced biological phosphorus removal system - Liping Chen; Xuhan Deng; Xiaojing Xie; Kaiying Wang; Hang Chen; Sheqi Cen; Fu Huang; Cenchao Wang; Yaqian Li; Chaohai Wei; Guanglei Qiu (Water Research, 2024)

A two-stage coordinated restoration scheme of hybrid AC/DC distribution grid considering cold load pickup and resilience enhancement - Hang Yu; Fu Xiao; Hanbei Zhang; Wei Liao; Yanxue Li (Sustainable Cities and Society, 2024)

AHR activation relieves deoxynivalenol-induced disruption of porcine intestinal epithelial barrier functions - Zi-Yan Hu; Shang-Jia Yang; Yuan-Hang Chang; Xue-Qi Wang; Rui-Qi Liu; Fu-Wei Jiang; Ming-Shan Chen; Jia-Xin Wang; Shuo Liu; Hong-Mei Zhu; Yu-Sheng Shi; Yi Zhao; et al. (Journal of Hazardous Materials, 2024)

HyperDehazing: A hyperspectral image dehazing benchmark dataset and a deep learning model for haze removal - Hang Fu; Ziyan Ling; Genyun Sun; Jinchang Ren; Aizhu Zhang; Li Zhang; Xiuping Jia (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Comprehensive assessment of rice bran dietary fiber on gut microbiota composition and metabolism during in vitro fermentation - Jingni Cheng; Kai Ye; Chujing Fu; Yu Zhou; Yang Chen; Gaoxing Ma; Shiguo Chen; Jie Tu; Hang Xiao (Food Research International, 2024)

Tower-based profiles of wintertime secondary organic aerosols in the urban boundary layer over Guangzhou - Yao Li; Hong Ren; Shengzhen Zhou; Chenglei Pei; Min Gao; Yuxuan Liang; Dian Ye; Xijing Sun; Fenghua Li; Jun Zhao; Jian Hang; Shaojia Fan; et al. (Science of The Total Environment, 2024)

Revisiting the estimation indicator for HONO emissions from light-duty vehicles - Xinping Yang; Mingliang Fu; Songdi Liao; Zhipeng Tu; Weijie Feng; Yunjing Wang; Han Jiang; Qili Tian; Hang Yin; Junyu Zheng; Yan Ding (Journal of Hazardous Materials, 2024)

Influences of released humic acids during thermal hydrolysis on sludge anaerobic digestion: New insights from the molecular weight of humic acids - Yaya Sun; Hongbo Liu; Jiaxin Wen; Hang Xiao; Mingze Shi; Xinlei Lu; Kai Shen; Xuedong Zhang; Bo Fu; Minhua Cui; Yajie Li; Salma Tabassum; et al. (Journal of Environmental Management, 2024)

Shifts in reproductive strategies in the evolutionary trajectory of plant lineages - Xin-Jian Zhang; Xian-Han Huang; Jacob B. Landis; Quan-Sheng Fu; Jun-Tong Chen; Peng-Rui Luo; Li-Juan Li; Heng-Yi Lu; Hang Sun; Tao Deng (Science China Life Sciences, 2024)

A Theoretical Model for the Hydraulic Permeability of Clayey Sediments Considering the Impact of Pore Fluid Chemistry - Lixue Cao; Hang Zhao; Baokai Yang; Jian Zhang; Hongzhi Song; Xiaomin Fu; Lele Liu (Journal of Marine Science and Engineering, 2024)
The chemistry of the pore fluid within clayey sediments frequently changes in various processes. However, the impacts of pore fluid chemistry have not been well included in the hydraulic permeability model, and the physical bases behind the salinity sensitivity of the hydraulic permeability remains elusive. In this study, a theoretical model for the hydraulic permeability of clayey sediments is proposed, and impacts of the pore fluid chemistry are quantitatively considered by introducing electrokinetic flow theory. Available experimental data were used to verify the theoretical model, and the verified model was further applied as a sensitivity analysis tool to explore more deeply how hydraulic permeability depends on pore fluid chemistry under different conditions. Coupling effects of pore water desalination and the effective stress enhancement on the hydraulic permeability of marine sediments surrounding a depressurization wellbore during hydrate production are discussed. Results and discussion show that the hydraulic permeability reduction is significant only when the electric double layer thickness is comparable to the characteristic pore size, and the reduction becomes more obvious when the ion mobility of the saline solution is smaller and the surface dielectric potential of clay minerals is lower. During gas hydrate production in the ocean, the salinity sensitivity of the hydraulic permeability could become either stronger and weaker, depending on whether the original characteristic pore size of marine sediments is relatively large or small.

Integrated transcriptomic and metabolomic analysis reveals the underlying mechanisms for male reproductive toxicity of polystyrene nanoplastics in mouse spermatocyte-derived GC-2spd(ts) cells - Hang Han; Zhen Zhang; Bo Xu; Liyang Ding; Hong Yang; Tiantian He; Xing Du; Xiuying Pei; Xufeng Fu (Toxicology in Vitro, 2024)

Pyrolysis-catalysis of waste tire to enhance the aromatics selectivity via metal-modified ZSM-5 catalysts - Boyu Qu; Ye Shui Zhang; Tian Wang; Hang Seok Choi; Yutao Zhang; Zegang Fu; Aimin Li; Guozhao Ji (Process Safety and Environmental Protection, 2024)

The resistance mechanism of humic acids and proteins in soluble microbial products from activated sludge against silver nanoparticles - Jia Kang; Yi-hang Wang; Yao-wen Zhang; Chu-qiong Song; Ao-di Wang; Ning Zhou; Yi-hui Zhang; Fa-zhan Li; Shu-li Liu; Li-sha Liu; Gang-fu Song; Bai-hong Wang (Journal of Environmental Chemical Engineering, 2024)

Relating the carbon sources to denitrifying community in full-scale wastewater treatment plants - Jinling Chen; Xia Tang; Xuewei Wu; Biping Li; Xia Tang; Xueran Lin; Pengfei Li; Hang Chen; Fu Huang; Xuhan Deng; Xiaojing Xie; Chaohai Wei; et al. (Chemosphere, 2024)

Tracking social-economic system nitrogen flow in China for emissions reduction and efficiency improvement - Hang Fu; Xin Xie; Kai Zhao; Dingjiang Chen; Shanying Hu; Yuanhang Li; Shoujuan Tang; Lei Shi (Resources, Conservation and Recycling, 2024)

The acceleration of the active phase transition of NiCoFe hydroxide by Ta doping to achieve Long-Time seawater electrolysis at Ampere-Level current density - Sanjiang Pan; Zishuo Xie; Hang Li; Shenao Wang; Yang Fu; Desong Wang (Fuel, 2024)

Engineering marine phospholipid nanoliposomes via glycerol-infused proliposomes: Mechanisms, strategies, and versatile applications in scalable food-grade nanoliposome production - Dong-wen Fu; Hang Xu; Rui-qi Sun; Xue-li Liu; Zhe Ji; Da-yong Zhou; Liang Song (Food Chemistry, 2024)

Modelling the dynamic gas/particle partitioning process of semi-volatile organic compounds emitted from point sources: Quantitative analysis and impact assessment - Fu-Jie Zhu; Li-Fu Wang; Long-Ze Qu; Wan-Li Ma; Geng-Bo Ren; Ben-Hang Li; Xiao-Dong Ma (Science of The Total Environment, 2024)

The distribution and fate of pesticides in full-scale drinking water treatment plants - Hui Tao; Junjie Fu; Yunxin Luo; Kailun Sun; Tao Lin; Hang Xu; Mingmei Ding (Journal of Water Process Engineering, 2024)

Occurrence, distribution, and ecological risk assessment of pharmaceuticals and personal care products in the surface water of Lipu River, China - Yanan Zhang; Guibin Huang; Qin Zhang; Xiaoqian Bi; Hang Chu; Zixuan Liu; Jun Luo; Shaoyuan Bai; Shengpeng Mo; Hui Wang; Mingming Fu (Environmental Research, 2024)

Intestinal metabolite xylulose inhibits colorectal cancer by inducing apoptosis through the MAPK signalling pathway - Qing Hu; Qiao Zheng; Xinhao Du; Ziyi Yang; Qian Tian; Lanfan Liang; Xinyu Zhao; Hang Bai; Yanqin Liu; Ming Zhao; Xiangsheng Fu (Toxicology and Applied Pharmacology, 2024)

Pickering extremulsion rich in lipophilic phytochemicals: Preparation, characterization and application - Xu Han; Cong-Jia Duan; Zi-Fei Wei; Jian Xu; Cheng-Dong Nie; Yuan-Hang Chang; Bo-wen Zhai; Yu-Jie Fu (Journal of Food Engineering, 2024)

Effect of tannic acid binding on the thermal degradation behavior and product toxicity of boscalid - Shaofeng Yuan; Jian Yang; Xiaoyan Fu; Hang Yu; Yahui Guo; Yunfei Xie; Yuan Xiao; Yuliang Cheng; Weirong Yao (Food Chemistry, 2024)

Discharge evolution law of debris flow based on a sharp bend physical modeling test - Ming Lu; Hao Sun; Jinfeng Liu; Abrar Hussain; Yuqi Shang; Hang Fu (Journal of Mountain Science, 2024)

Novel method for identifying the heaviest QED atom - Jing-Hang Fu; Sen Jia; Xing-Yu Zhou; Yu-Jie Zhang; Cheng-Ping Shen; Chang-Zheng Yuan (Science Bulletin, 2024)

Spatiotemporal evolution of air cargo networks and its impact on economic development - An analysis of China's domestic market before and during the COVID-19 pandemic - Hang He; Hanjun Wu; Kan Wai Hong Tsui; Biao Wang; Xiaowen Fu (Journal of Transport Geography, 2024)

Evolutionary correlates of extinction risk in Chinese angiosperm - Yaojun Ye; Quansheng Fu; Sergei Volis; Zhimin Li; Hang Sun; Tao Deng (Biological Conservation, 2024)

Nrf2-mediated ferroptosis of spermatogenic cells involved in male reproductive toxicity induced by polystyrene nanoplastics in mice - Xufeng Fu; Hang Han; Hong Yang; Bo Xu; Wenjie Dai; Ling Liu; Tiantian He; Xing Du; Xiuying Pei (Journal of Zhejiang University-SCIENCE B, 2024)

Association between PM10 pollution and the hospitalization of chronic obstructive pulmonary disease with comorbidity: evidence in 17 cities of Henan, Central China - Yanran Duan; Hang Fu; Shuai Jiang; Zhao Yin; Sufan Wang; Jinghong Gao; Mengyu Yang; Suxian Wang; Zihan Mu; Changying Chen; Yaojun Zhao; Chengzeng Wang (International Journal of Biometeorology, 2024)

Synthesizing cationic polymers and tuning their properties for microalgae harvesting - Lisa Aditya; Hang P. Vu; Md Abu Hasan Johir; Shudi Mao; Ashley Ansari; Qiang Fu; Long D. Nghiem (Science of The Total Environment, 2024)

Effects of intensive chlorine disinfection on nitrogen and phosphorus removal in WWTPs - Yixing Zhang; Xueran Lin; Tang Xia; Hang Chen; Fu Huang; Chaohai Wei; Guanglei Qiu (Science of The Total Environment, 2024)

Characterizing NOx emissions from diesel trucks with tampered aftertreatment systems and its implications for identifying high emitters - Miao Tian; Liqiang He; Di Peng; Mingliang Fu; Shuai Ma; Jinsong Mu; Quanshun Yu; Jia Wang; Hang Yin; Junfang Wang (Science of The Total Environment, 2024)

Increased precipitation alters the effects of nitrogen deposition on soil bacterial and fungal communities in a temperate forest - Yang Liu; Hang Wang; Xiangping Tan; Shenglei Fu; Dan Liu; Weijun Shen (Science of The Total Environment, 2024)

Deciphering exogenous chemical carcinogenicity through interpretable deep learning: A novel approach for evaluating atmospheric pollutant hazards - Huazhou Zhang; Hang Yi; Yuxing Hao; Lu Zhao; Wenxiao Pan; Qiao Xue; Xian Liu; Jianjie Fu; Aiqian Zhang (Journal of Hazardous Materials, 2024)

CatNet: Sequence-based deep learning with cross-attention mechanism for identifying endocrine-disrupting chemicals - Lu Zhao; Qiao Xue; Huazhou Zhang; Yuxing Hao; Hang Yi; Xian Liu; Wenxiao Pan; Jianjie Fu; Aiqian Zhang (Journal of Hazardous Materials, 2024)

Curcumin inhibits the development of colorectal cancer via regulating the USP4/LAMP3 pathway - Hai Wei; Xianzhe Li; Fu Liu; Yuan Li; Bin Luo; Xin Huang; Hang Chen; Bo Wen; Pei Ma (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Multi-scale failure mechanisms of hydraulic engineering exposed to seasonally frozen salinization environment: Integrating SBAS-InSAR and mechanical experiments - Zhaoxi Wang; Chen Cao; Qingbo Yu; Qing Wang; Cencen Niu; Jiejie Shen; Kuanxing Zhu; Jing Liu; Mengxia Han; Huicheng Fu; Xun Sun; Weitong Xia; et al. (Science of The Total Environment, 2024)

Assessment of identification performance for high emission heavy-duty diesel vehicles by means of remote sensing - Han Jiang; Junfang Wang; Miao Tian; Chen Zhao; Yingzhi Zhang; Xiaohu Wang; Jin Liu; Mingliang Fu; Hang Yin; Yan Ding (Science of The Total Environment, 2024)

Process optimization, thermal hazard evaluation and reaction mechanism of m-xylene nitration using HNO3-Ac2O as nitrating reagent - Hang Yao; Gang Fu; Yuqing Ni; Lei Ni; Juncheng Jiang; Han Zhang; Zhen Cheng; Zhiquan Chen (Process Safety and Environmental Protection, 2024)

AaABCG20 transporter involved in cutin and wax secretion affects the initiation and development of glandular trichomes in Artemisia annua - Xueqing Fu; Han Zheng; Yuting Wang; Hang Liu; Pin Liu; Ling Li; Jingya Zhao; Xiaofen Sun; Kexuan Tang (Plant Science, 2024)

The dynamic mechanism of scientific and technological innovation in China’s marine biomedical industry - Xiu-Mei Fu; Yan-Xin Tan; Ying Liu; Ying-Hui Han; Qiao-Qiao Qi; Jing-Hang Li; Chun-Yu Lin (Frontiers in Marine Science, 2024)
As one of the important forces promoting the development of the marine economy, the marine biomedical industry (MBI) shows typical knowledge and technology-intensive characteristics. It is of great significance to explore the industrial innovation dynamic mechanism for breaking through the bottleneck of innovative development as well as achieving high-quality development. This paper constructed a system dynamics model for scientific and technological innovation (STI) in the MBI and then explored the dynamic mechanism of STI in the industry through simulation. The study found that, in the innovation environment subsystem, the two factors of the intellectual property protection intensity and the government’s scientific research funding input had the most significant positive driving effects on STI of the MBI; the promotion of government education funding input showed a significant strengthening trend over time, while the marine environmental regulation intensity had comparatively little effect on the level of STI. In the subsystem of innovation input, both innovation funding input and innovation personnel input were the direct driving forces for the improvement of the STI level. And enterprises played a dominant role in STI because the STI level of the MBI was more sensitive to the changes in enterprise innovation input. Compared with the individual factor input, the synergistic promotion effect of multiple factors is more significant. In addition, it was found that there was a low conversion rate of scientific research achievements in China’s MBI by analyzing the influence of various factors changing on technological output and economic output. Based on the research results, this paper puts forward corresponding policy suggestions in order to provide theoretical support and a practical basis for promoting the technological innovation level of China’s MBI as well as references for other countries.

Twelve pathways of carbon neutrality for industrial parks - Yuheng Sun; Yuanhang Li; Jun Ning; Hang Fu; Fangtao Liu; Zhengyuan Feng; Guangxin Liu; Lei Shi (Journal of Cleaner Production, 2024)

Upcycling spent lithium battery cathodes into efficient PMS catalysts for organic contaminants degradation - Lei Xu; Le Liang; Chen Chen; Ze-Hang Chen; Zong-Bin Lv; Ming-Lai Fu; Baoling Yuan (Journal of Environmental Chemical Engineering, 2023)

The hepatoprotective effects of plant-based foods based on the “gut–liver axis”: a prospective review - Qiongdan Hu; Wan Liao; Zhen Zhang; Sanjun Shi; Shuguang Hou; Ningping Ji; Xinjie Zhang; Qian Zhang; Yangyang Liao; Linghui Li; Zongping Zhu; Yi Chen; et al. (Critical Reviews in Food Science and Nutrition, 2023)

Candidatus Accumulibacter use fermentation products for enhanced biological phosphorus removal - Liping Chen; Gengrui Wei; Yushen Zhang; Kaiying Wang; Cenchao Wang; Xuhan Deng; Yaqian Li; Xiaojing Xie; Jinling Chen; Fu Huang; Hang Chen; Bin Zhang; et al. (Water Research, 2023)

Stability evaluation of salt cavern hydrogen storage and optimization of operating parameters under high frequency injection production - De-Peng Li; Wei Liu; Pan Fu; Lin Li; Fan-Sheng Ban; Qi-Hang Li; Jin-Yang Fan; De-Yi Jiang; Zhi-Xin Zhang (Gas Science and Engineering, 2023)

Polyphenols modulate microalgae metabolism with a particular increment in lipid accumulation - Li-Gong Zou; Dan-Lin Zheng; Yi-Tong Yao; Fu-Fang Wen; Da-Wei Li; Yu-Feng Yang; Wei-Dong Yang; Srinivasan Balamurugan; Hang Fai Kwok; Hong-Ye Li (Fuel, 2023)

Comprehensive assessment of Hypsizygus marmoreus polysaccharides through simulated digestion and gut microbiota fermentation in vitro - Kai Ye; Chujing Fu; Sai Ma; Hengjun Du; Shiguo Chen; Donghong Liu; Gaoxing Ma; Hang Xiao (Food Hydrocolloids, 2023)

Association between prenatal exposure to per- and polyfluoroalkyl substances and neurodevelopment in children: Evidence based on birth cohort - Xin-xin Gao; Qian-lin Zuo; Xi-hang Fu; Ling-ling Song; Man-qiu Cen; Jing Wu (Environmental Research, 2023)

Thermodynamic and kinetic analyses of Janus membrane scaling in membrane distillation for zero liquid discharge engineering - Ao Wang; Hang Xu; Jun Ma; Jiawei Fu; Tao Lin; Mingmei Ding (Desalination, 2023)

Refractory black carbon aerosols in rainwater in the summer of 2019 in Beijing: Mass concentration, size distribution and wet scavenging ratio - Shandong Lei; Baozhu Ge; Hang Liu; Jiannong Quan; Danhui Xu; Yuting Zhang; Weijie Yao; Lu Lei; Yu Tian; Qi Liao; Xiaoyong Liu; Jie Li; et al. (Journal of Environmental Sciences, 2023)

The selective activator protein-1 inhibitor T-5224 regulates the IRF4/MYC axis and exerts cooperative antimyeloma activity with bortezomib - Sishi Tang; Fangrong Zhang; Jian Li; Hang Dong; Qin Yang; Jing Liu; Yunfeng Fu (Chemico-Biological Interactions, 2023)

A pan-coronavirus peptide inhibitor prevents SARS-CoV-2 infection in mice by intranasal delivery - Lili Wu; Anqi Zheng; Yangming Tang; Yan Chai; Jiantao Chen; Lin Cheng; Yu Hu; Jing Qu; Wenwen Lei; William Jun Liu; Guizhen Wu; Shaogui Zeng; et al. (Science China Life Sciences, 2023)

Geochronology and petrogenesis of the early Silurian Zeluo mafic-ultramafic intrusion, eastern Tibet: implications for the tectonic setting and evolution of the eastern Proto-Tethys Ocean - Hang Zhou; Wenxiao Zhou; Ernest Chi Fru; Thomas C. Sheldrick; Haiquan Li; Bo Huang; Dong Fu; Yadong Xu (International Geology Review, 2023)

Reduction potential of vehicular emission in Chengdu, China: A case study of COVID-19 - Xinping Yang; Hefeng Zhang; Wei Li; Hong Tian; Yongdong Wang; Jing Zhou; Ze Bao; Xiaorui Chen; Teng Xiao; Yunjing Wang; Mingliang Fu; Xian Wu; et al. (Urban Climate, 2023)

Dictamnine suppresses the development of pear ring rot induced by Botryosphaeria dothidea infection by disrupting the chitin biosynthesis - Minxuan Yuan; Xiaogui Liang; Duantao Cao; Hongliang Wu; Suling Xiao; Hui Liang; Hang Li; Yingjin Huang; Hongyi Wei; Wenwen Peng; Xiaoxiang Fu (Pesticide Biochemistry and Physiology, 2023)

Exhaust aftertreatment device-derived ammonia emissions from conventional and hybrid light-duty gasoline vehicles over different driving cycles - Han Jiang; Hefeng Zhang; Haiguang Zhao; Mingliang Fu; Yunjing Wang; Xian Wu; Xinping Yang; Jianglin Ji; Hang Yin; Yan Ding (Journal of Hazardous Materials, 2023)

Piriformospora indica alter root-associated microbiome structure to enhance Artemisia annua L. tolerance to arsenic - Saeed ur Rahman; Muhammad Khalid; Nan Hui; Asad Rehman; Sadaf-Ilyas Kayani; Xueqing Fu; Han Zheng; Jin Shao; Abid Ali Khan; Mehran Ali; Ayat Taheri; Hang Liu; et al. (Journal of Hazardous Materials, 2023)

Three-dimensional singular spectrum analysis for precise land cover classification from UAV-borne hyperspectral benchmark datasets - Hang Fu; Genyun Sun; Li Zhang; Aizhu Zhang; Jinchang Ren; Xiuping Jia; Feng Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Research on effects of rolling motion on a pressurizer surge line based on the fluid-solid-thermal coupling method - Hang Yu; Xinwen Zhao; Shengwei Fu; Kang Zhu (Annals of Nuclear Energy, 2023)

Examination of long-time aging process on volatile organic compounds emitted from solid fuel combustion in a rural area of China - Kun He; Tao Fu; Bin Zhang; Hongmei Xu; Jian Sun; Haijiang Zou; Zhou Zhang; Steven Sai Hang Ho; Junji Cao; Zhenxing Shen (Chemosphere, 2023)

Simulated gastrointestinal digestion and gut microbiota fermentation of polysaccharides from Agaricus bisporus - Chujing Fu; Kai Ye; Sai Ma; Hengjun Du; Shiguo Chen; Donghong Liu; Gaoxing Ma; Hang Xiao (Food Chemistry, 2023)

Exploring the beneficial effects and mechanisms of Cerasus humilis (Bge.) Sok fruit for calcium supplementation and promotion - Hang Li; Jiahui Yue; Wenxin Xia; TingTing Li; Xiaofen Huang; Yuanyuan Zhang; Xueyan Fu (Food Bioscience, 2023)

Coupled behaviour and strength prediction of tapered CFDST columns with large hollow ratios for wind turbine towers - Ran Deng; Xu-Hong Zhou; Wei-Dong Ji; Rong-Fu Li; Shuai-Quan Zheng; Yu-Hang Wang (Engineering Structures, 2023)

Process hazard and thermal risk evaluation of m-xylene nitration with mixed acid - Hang Yao; Lei Ni; Yinshan Liu; Gang Fu; Juncheng Jiang; Zhen Cheng; Yuqing Ni; Zhiquan Chen (Process Safety and Environmental Protection, 2023)

The PIWI-specific insertion module helps load longer piRNAs for translational activation essential for male fertility - Xin Wang; Di-Hang Lin; Yue Yan; An-Hui Wang; Jiaoyang Liao; Qian Meng; Wen-Qing Yang; Heng Zuo; Min-Min Hua; Fengjuan Zhang; Hongwen Zhu; Hu Zhou; et al. (Science China Life Sciences, 2023)

Daphnia magna uptake and excretion of luminescence‐labelled polystyrene nanoparticle as visualized by high sensitivity real-time optical imaging - Yu-Hang Zhang; Rong-Yao Gao; Ze-Jun Wang; Qian-Qian Shao; Ya-Wen Hu; Hua-Bing Jia; Xiao-Jing Liu; Feng-Qin Dong; Li-Min Fu; Jian-Ping Zhang (Chemosphere, 2023)

Ca–La layered double hydroxide (LDH) for selective and efficient removal of phosphate from wastewater - Yuhang Cao; Xuewei Wu; Biqing Li; Xia Tang; Xueran Lin; Pengfei Li; Hang Chen; Fu Huang; Chaohai Wei; Jian Wei; Guanglei Qiu (Chemosphere, 2023)

Sustainable production of drop-in butyric acid from bioderived poly(3-hydroxybutyrate) - Shimin Kang; Jianhao Liang; Jinxia Fu; Jiaqi Feng; Zaiming Tan; Zizhi Huang; Hang Zhang; Yongjun Xu (Sustainable Chemistry and Pharmacy, 2023)

Preparation and application of red mud-based zero-valent iron heterogeneous Fenton catalyst: A new idea for red mud recycling - Hang Li; Bofang Shi; Xiaojie Fu; Haowen Zhang; Honghui Yang (Journal of Environmental Chemical Engineering, 2023)

Genome-wide Association Study of Root Hair Length in Maize - Li Xuhui; Lu Siqi; Chen Weiwei; Zhu Hang; Lin Huanzhang; Fu Danwen; Fan Lina; Fang Junteng; Hu Yuanqiang; Zhang Xiangbo; Chang Hailong; Qi Yongwen (Tropical Plant Biology, 2023)

Prenatal diagnosis in the fetal hyperechogenic kidneys: assessment using chromosomal microarray analysis and exome sequencing - Ruibin Huang; Fang Fu; Hang Zhou; Lu Zhang; Tingying Lei; Ken Cheng; Shujuan Yan; Fei Guo; You Wang; Chunling Ma; Ru Li; Qiuxia Yu; et al. (Human Genetics, 2023)

Impacts on real-world extra cold start emissions: Fuel injection, powertrain, aftertreatment and ambient temperature - Xian Wu; Haiguang Zhao; Liqiang He; Xinping Yang; Han Jiang; Mingliang Fu; Hang Yin; Yan Ding (Environmental Pollution, 2023)

Multi-scale spectral-spatial dual-transformer network for hyperspectral image classification - Zhaojie Pan; Sunjinyan Ding; Genyun Sun; Aizhu Zhang; Xiuping Jia; Hang Fu (International Journal of Remote Sensing, 2023)

Sulfur dioxide may predominate in the adverse effects of ambient air pollutants on semen quality among the general population in Hefei, China - Feng Zhang; Hang Li; Wenting Xu; Ge Song; Zhanpeng Wang; Xiaohong Mao; Yiqiu Wei; Mengyang Dai; Yuying Zhang; Qunshan Shen; Feifei Fu; Jing Tan; et al. (Science of The Total Environment, 2023)

AaWIN1, an AP2/ERF protein, positively regulates glandular secretory trichome initiation in Artemisia annua - Chen Wang; Tiantian Chen; Yongpeng Li; Hang Liu; Wei Qin; Zhangkuanyu Wu; Bowen Peng; Xiuyun Wang; Xin Yan; Xueqing Fu; Ling Li; Kexuan Tang (Plant Science, 2023)

An ultrasensitive FET biosensor based on vertically aligned MoS2 nanolayers with abundant surface active sites - Pengfei Song; Pengfei Ou; Yongjie Wang; Hang Yuan; Sixuan Duan; Longyan Chen; Hao Fu; Jun Song; Xinyu Liu (Analytica Chimica Acta, 2023)

A hybrid deep learning model for regional O3 and NO2 concentrations prediction based on spatiotemporal dependencies in air quality monitoring network - Cui-lin Wu; Hong-di He; Rui-feng Song; Xing-hang Zhu; Zhong-ren Peng; Qing-yan Fu; Jun Pan (Environmental Pollution, 2023)

Tailoring the crumpled structures of a polyamide membrane with a heterostructural MXene-TiO2 interlayer for high water permeability - Jiawei Fu; Hang Xu; Tao Lin; Ao Wang; Anqi Wang; Chen Yao; Weihang Chen; Mingmei Ding; Chunxia Geng; Li Gao (Desalination, 2023)

Whole exome sequencing improves genetic diagnosis of fetal clubfoot - Ruibin Huang; Hang Zhou; Chunling Ma; Fang Fu; Ken Cheng; You Wang; Ru Li; Tingying Lei; Qiuxia Yu; Dan Wang; Shujuan Yan; Xin Yang; et al. (Human Genetics, 2023)

A novel ternary deep eutectic solvent pretreatment for the efficient separation and conversion of high-quality gutta-percha, value-added lignin and monosaccharide from Eucommia ulmoides seed shells - Cong-Jia Duan; Xu Han; Yuan-Hang Chang; Jian Xu; Gan-Lu Yue; Ying Zhang; Yu-Jie Fu (Bioresource Technology, 2023)

Genome sequence and comparative analysis of fungal antagonistic strain Bacillus velezensis LJBV19 - Bo Wang; Bohan Yang; Hang Peng; Jiang Lu; Peining Fu (Folia Microbiologica, 2023)

Monitoring of tree tilt motion using lorawan-based wireless tree sensing system (IoTT) during super typhoon Mangkhut - Wai Yi Chau; Yu-Hsing Wang; Siu Wai Chiu; Pin Siang Tan; Mei Ling Leung; Hoi Lun Lui; Jimmy Wu; Yun Man Lau; Kuan-Fu Liu; Billy Chi Hang Hau (Agricultural and Forest Meteorology, 2023)

Synergistic multi-altimeter for estimating water level in the coastal zone of Beibu Gulf using SEL, ALES + and BFAST algorithms - Jiaoling Qin; Sunzhe Li; Hang Yao; Bolin Fu; Hongchang He; Feng Wang; Lilong Liu; Donglin Fan; Xu He; Yuyang Li (Frontiers in Marine Science, 2023)
Accurately monitoring and predicting the large-scale dynamic changes of water levels in coastal zones is essential for its protection, restoration and sustainable development. However, there has been a challenge for achieving this goal using a single radar altimeter and retracking technique due to the diversity and complexity of coastal waveforms. To solve this issue, we proposed an approach of estimating water level of the coastal zone in Beibu Gulf, China, by combination of waveform classifications and multiple sub-waveform retrackers. This paper stacked Random Forest (RF), XGBoost and CatBoost algorithms for building an ensemble learning (SEL) model to classify coastal waveforms, and further evaluated the performance of three retracking strategies in refining waveforms using Cryosat-2, SARAL, Sentinel-3 altimeters. We compared the estimation accuracy of the coastal water levels between the single altimeter and synergistic multi-altimeter, and combined Breaks for Additive Season and Trend (BFAST), Mann-Kendall mutation test (MK) with Long Short-Term Memory (LSTM) algorithms to track the historical change process of coastal water levels, and predict its future development trend. This paper found that: (1) The SEL algorithm achieved high-precision classification of different coastal waveforms with an average accuracy of 0.959, which outperformed three single machine learning algorithms. (2) Combination of Threshold Retracker and ALES+ Retracker (TR_ALES+) achieved the better retracking quality with an improvement of correlation coefficient (R, 0.089~0.475) and root mean square error (RMSE, 0.008∼ 0.029 m) when comparing to the Threshold Retracker & Primary Peak COG Retracker and Threshold Retracker & Primary Peak Threshold Retracker. (3) The coastal water levels of Cryosat-2, SARAL, Sentinel-3 and multi-altimeter were in good agreement (R>0.66, RMSE<0.135m) with Copernicus Climate Change Service (C3S) water level. (4) The coastal water levels of the Beibu Gulf displayed a slowly rising trend from 2011 to 2021 with an average annual growth rate of 8mm/a, its lowest water level focused on May-August, the peak of water level was in October-November, and the average annual growth rate of water level from 2022-2031 was about 0.6mm/a. These results can provide guidance for scientific monitoring and sustainable management of coastal zones.

Enhanced high-salinity brines treatment using polyamide nanofiltration membrane with tunable interlayered MXene channel - Ao Wang; Hang Xu; Jiawei Fu; Tao Lin; Jun Ma; Mingmei Ding; Li Gao (Science of The Total Environment, 2023)

Recent advances and perspectives towards emission inventories of mobile sources: Compilation approaches, data acquisition methods, and case studies - Han Jiang; Hefeng Zhang; Mingliang Fu; Zhihui Huang; Hong Ni; Hang Yin; Yan Ding (Journal of Environmental Sciences, 2023)

Association between pyrethroid exposure and risk of depressive symptoms in the general US adults - Hui-ru Li; Xi-hang Fu; Ling-ling Song; Man-qiu Cen; Jing Wu (Environmental Science and Pollution Research, 2023)

Transport Patterns and Potential Sources of Atmospheric Pollution during the XXIV Olympic Winter Games Period - Yuting Zhang; Xiaole Pan; Yu Tian; Hang Liu; Xueshun Chen; Baozhu Ge; Zhe Wang; Xiao Tang; Shandong Lei; Weijie Yao; Yuanzhe Ren; Yongli Tian; et al. (Advances in Atmospheric Sciences, 2022)
The attainment of suitable ambient air quality standards is a matter of great concern for successfully hosting the XXIV Olympic Winter Games (OWG). Transport patterns and potential sources of pollutants in Zhangjiakou (ZJK) were investigated using pollutant monitoring datasets and a dispersion model. The PM 2.5 concentration during February in ZJK has increased slightly (28%) from 2018 to 2021, mostly owing to the shift of main potential source regions of west-central Inner Mongolia and Mongolian areas (2015–18) to the North China Plain and northern Shanxi Province (NCPS) after 2018. Using CO as an indicator, the relative contributions of the different regions to the receptor site (ZJK) were evaluated based on the source-receptor-relationship method (SRR) and an emission inventory. We found that the relative contribution of pollutants from NCPS increased from 33% to 68% during 2019–21. Central Inner Mongolia (CIM) also has an important impact on ZJK under unfavorable weather conditions. This study demonstrated that the effect of pollution control measures in the NCPS and CIM should be strengthened to ensure that the air quality meets the standard during the XXIV OWG.

Establishment and identification of six wheat-Thinopyrum ponticum disomic addition lines derived from partial amphiploid Xiaoyan 7430 - Hongwei Jia; Hang Feng; Guotang Yang; Hongwei Li; Shulan Fu; Bin Li; Zhensheng Li; Qi Zheng (Theoretical and Applied Genetics, 2022)

Correction to: Inhibition of Dectin-1 Ameliorates Neuroinflammation by Regulating Microglia/Macrophage Phenotype After Intracerebral Hemorrhage in Mice - Xiongjie Fu; Hanhai Zeng; Jikuang Zhao; Guoyang Zhou; Hang Zhou; Jianfeng Zhuang; Chaoran Xu; Jianru Li; Yucong Peng; Yang Cao; Yin Li; Huaijun Chen; et al. (Translational Stroke Research, 2022)

Modified Hoek–Brown failure criterion for anisotropic intact rock under high confining pressures - Zefan Wang; Chengzhi Qi; Liren Ban; Hang Yu; Haonan Wang; Ziming Fu (Bulletin of Engineering Geology and the Environment, 2022)

A novel anticancer property of Lycium barbarum polysaccharide in triggering ferroptosis of breast cancer cells - Xing Du; Jingjing Zhang; Ling Liu; Bo Xu; Hang Han; Wenjie Dai; Xiuying Pei; Xufeng Fu; Shaozhang Hou (Journal of Zhejiang University-SCIENCE B, 2022)

Neutrophil Extracellular Traps may be a Potential Target for Treating Early Brain Injury in Subarachnoid Hemorrhage - Hanhai Zeng; Xiongjie Fu; Jing Cai; Chenjun Sun; Mengyan Yu; Yucong Peng; Jianfeng Zhuang; Jingyin Chen; Huaijun Chen; Qian Yu; Chaoran Xu; Hang Zhou; et al. (Translational Stroke Research, 2022)

Inhibition of Dectin-1 Ameliorates Neuroinflammation by Regulating Microglia/Macrophage Phenotype After Intracerebral Hemorrhage in Mice - Xiongjie Fu; Hanhai Zeng; Jikuang Zhao; Guoyang Zhou; Hang Zhou; Jianfeng Zhuang; Chaoran Xu; Jianru Li; Yucong Peng; Yang Cao; Yin Li; Huaijun Chen; et al. (Translational Stroke Research, 2021)

Pharmacological Activation of RXR-α Promotes Hematoma Absorption via a PPAR-γ-dependent Pathway After Intracerebral Hemorrhage - Chaoran Xu; Huaijun Chen; Shengjun Zhou; Chenjun Sun; Xiaolong Xia; Yucong Peng; Jianfeng Zhuang; Xiongjie Fu; Hanhai Zeng; Hang Zhou; Yang Cao; Qian Yu; et al. (Neuroscience Bulletin, 2021)

A proteomic analysis of Bcl-2 regulation of cell cycle arrest: insight into the mechanisms - Xing Du; Jingjing Xiao; Xufeng Fu; Bo Xu; Hang Han; Yin Wang; Xiuying Pei (Journal of Zhejiang University-SCIENCE B, 2021)

qTGW12a, a naturally varying QTL, regulates grain weight in rice - Zhixuan Du; Zhou Huang; Jianbin Li; Jianzhong Bao; Hang Tu; Chuihai Zeng; Zheng Wu; Haihui Fu; Jie Xu; Dahu Zhou; Changlan Zhu; Junru Fu; et al. (Theoretical and Applied Genetics, 2021)
Key message A stable QTL associated with rice grain type with a large effect value was found in multiple environments, and its candidate genes were verified by genetic transformation. Abstract Rice ( Oryza sativa L . ) grain size is critical to both yield and appearance quality. Therefore, the discovery and identification of rice grain size genes can provide pathways for the cultivation of high-yielding varieties. In the present work, 45,607 SNP markers were used to construct a high-density genetic map of rice recombinant inbred lines, and hence a total of 14 quantitative trait loci (QTLs) were detected based on the phenotypic data of grain weight, grain length and grain width under four different environments. qTGW12a and qGL12 are newly detected QTLs related to grain weight, and are located between 22.43 Mb and 22.45 Mb on chromosome 12. Gene annotation shows that the QTL region contains the LOC_Os12g36660 annotated gene, which encodes the multidrug and toxic compound extrusion (MATE) transporter. Mutations in exons and the splice site were responsible for the changes in grain type and weight. Gene knockout experiments were used to verify these results. Hence, these results provide a basis for the cloning of qTGW12a . This discovery provides new insights for studying the genetic mechanism of rice grain morphology, and reveals a promising gene to ultimately increase rice yield.

Wogonin Accelerates Hematoma Clearance and Improves Neurological Outcome via the PPAR-γ Pathway After Intracerebral Hemorrhage - Jianfeng Zhuang; Yucong Peng; Chi Gu; Huihui Chen; Zheng Lin; Hang Zhou; Xiao Wu; Jianru Li; Xiaobo Yu; Yang Cao; Hanhai Zeng; Xiongjie Fu; et al. (Translational Stroke Research, 2021)

Microscopic pore-throat grading evaluation in a tight oil reservoir using machine learning: a case study of the Fuyu oil layer in Bayanchagan area, Songliao Basin central depression - Yilin Li; Daming Niu; Yunfeng Zhang; Haiguang Wu; Hang Fu; Zeqiang Wang (Earth Science Informatics, 2021)

Selective Ferroptosis Inhibitor Liproxstatin-1 Attenuates Neurological Deficits and Neuroinflammation After Subarachnoid Hemorrhage - Yang Cao; Yin Li; Chao He; Feng Yan; Jian-Ru Li; Hang-Zhe Xu; Jian-Feng Zhuang; Hang Zhou; Yu-Cong Peng; Xiong-Jie Fu; Xiao-Yang Lu; Yuan Yao; et al. (Neuroscience Bulletin, 2021)

Experimental Investigation on the Influence of Water Content on Mechanical Properties and Failure Characteristics of Tuff - Yanqi Song; Hongfa Ma; Xiangshang Li; Junjie Zheng; Minjian Yang; Hang Fu (Geotechnical and Geological Engineering, 2021)

Short-Term Visual Experience Leads to Potentiation of Spontaneous Activity in Mouse Superior Colliculus - Qingpeng Yu; Hang Fu; Gang Wang; Jiayi Zhang; Biao Yan (Neuroscience Bulletin, 2021)

A sensitive and rapid bacterial antibiotic susceptibility test method by surface enhanced Raman spectroscopy - Shijie Fu; Xiwen Wang; Ting Wang; Zhiping Li; Deming Han; Chunsheng Yu; Cui Yang; Han Qu; Hang Chi; Yutian Wang; Song Li; Baihui Tian; et al. (Brazilian Journal of Microbiology, 2020)

Complete genome sequence of a novel bovine hepacivirus from Yunnan, China - Xin Qiang; Xueying Shen; Honghong Peng; Xiaofang Guo; Zhihai He; Mingguo Yao; Guozhang Fu; Yujun Cui; Xianglilan Zhang; Yong Huang; Hang Fan; Chunhong Du; et al. (Archives of Virology, 2020)

Simultaneous roxarsone photocatalytic degradation and arsenic adsorption removal by TiO2/FeOOH hybrid - Wentao Fu; Dong-Lei Lu; Hang Yao; Shoujun Yuan; Wei Wang; Miao Gong; Zhen-Hu Hu (Environmental Science and Pollution Research, 2020)

Brain-Wide Shape Reconstruction of a Traced Neuron Using the Convex Image Segmentation Method - Shiwei Li; Tingwei Quan; Hang Zhou; Qing Huang; Tao Guan; Yijun Chen; Cheng Xu; Hongtao Kang; Anan Li; Ling Fu; Qingming Luo; Hui Gong; et al. (Neuroinformatics, 2020)

Detailed characterization of micronano pore structure of tight sandstone reservoir space in three dimensional space: a case study of the Gao 3 and Gao 4 members of Gaotaizi reservoir in the Qijia area of the Songliao basin - Yilin Li; Yunfeng Zhang; Hang Fu; Qiang Yan (Arabian Journal of Geosciences, 2020)

Major advances in studies of the physical geography and living environment of China during the past 70 years and future prospects - Fahu Chen; Bojie Fu; Jun Xia; Duo Wu; Shaohong Wu; Yili Zhang; Hang Sun; Yu Liu; Xiaomin Fang; Boqiang Qin; Xin Li; Tingjun Zhang; et al. (Science China Earth Sciences, 2019)

Identifying Weak Signals in Inhomogeneous Neuronal Images for Large-Scale Tracing of Sparsely Distributed Neurites - Shiwei Li; Tingwei Quan; Hang Zhou; FangFang Yin; Anan Li; Ling Fu; Qingming Luo; Hui Gong; Shaoqun Zeng (Neuroinformatics, 2019)

An iterative damped least-squares algorithm for simultaneously monitoring the development of hemorrhagic and secondary ischemic lesions in brain injuries - Xuechao Liu; Haoting Li; Hang Ma; Canhua Xu; Bin Yang; Meng Dai; Xiuzhen Dong; Feng Fu (Medical & Biological Engineering & Computing, 2019)

Late Cretaceous magmatism and porphyry Mo–Cu polymetallic mineralization in the Tongchanggou Intrusion, Geza Arc, Southwestern China - Xue-long Liu; Jian-hang Chen; Wen-chang Li; Na Zhang; Shuai-shuai Wang; Chang-zhen Zhang; Ying Luo; Zhen-huan Li; Fu-cheng Yang (Arabian Journal of Geosciences, 2019)

Pine needles as biomonitors of polybrominated diphenyl ethers and emerging flame retardants in the atmosphere of Shanghai, China: occurrence, spatial distributions, and possible sources - Hao-Hao Jia; Xue-Tong Wang; Hang-Xin Cheng; Ying Zhou; Rui Fu (Environmental Science and Pollution Research, 2019)

Stromatolites in Middle Ordovician carbonate–evaporite sequences and their carbon and sulfur isotopes stratigraphy, Ordos Basin, northwestern China - Fan-Wei Meng; Zhi-li Zhang; Xian-qin Yan; Pei Ni; Wen-Hang Liu; Fu Fan; Gu-Wei Xie (Carbonates and Evaporites, 2019)

Lacidipine Amorphous Solid Dispersion Based on Hot Melt Extrusion: Good Miscibility, Enhanced Dissolution, and Favorable Stability - Long Xi; Hang Song; Yunzhi Wang; Haoshi Gao; Qiang Fu (AAPS PharmSciTech, 2018)

Novel adefovir mono L-amino acid ester, mono bile acid ester derivatives: Design, synthesis, biological evaluation, and molecular docking study - Ya Chen; Wen Zheng Zhang; Jing Li; Tao Xiao; Jiang Xia Liu; Min Luo; Hang Su; Xiao-Zhong Fu; Ting Liu; Yong-Xi Dong; Yong-Long Zhao; Bin He; et al. (Medicinal Chemistry Research, 2017)

Activation of Parvalbumin-Positive Neurons in Both Retina and Primary Visual Cortex Improves the Feature-Selectivity of Primary Visual Cortex Neurons - Jinggang Duan; Hang Fu; Jiayi Zhang (Neuroscience Bulletin, 2017)

Permeability of novel 4′-N-substituted (aminomethyl) benzoate-7-substituted nicotinic acid ester derivatives of scutellarein in Caco-2 cells and in an in vitro model of the blood-brain barrier - Yu Ou; Min Luo; Yong-Xi Dong; Hang Su; Xiao-Zhong Fu; Yu-Feng Cha; Shun Zhang; Yong-Long Zhao; Yong-Jun Li; Yong-Lin Wang (Medicinal Chemistry Research, 2016)

CHD3 chromatin-remodeling factor PICKLE regulates floral transition partially via modulating LEAFY expression at the chromatin level in Arabidopsis - Xing Fu; Chaonan Li; Qing Liang; Yangyang Zhou; Hang He; Liu-Min Fan (Science China Life Sciences, 2016)

Enhanced degradation of benzene by percarbonate activated with Fe(II)-glutamate complex - Xiaori Fu; Xiaogang Gu; Shuguang Lu; Zhouwei Miao; Minhui Xu; Xiang Zhang; Muhammad Danish; Hang Cui; Usman Farooq; Zhaofu Qiu; Qian Sui (Environmental Science and Pollution Research, 2016)

A systematic approach to expound the variations in taxane production under different dissolved oxygen conditions in Taxus chinensis cells - Chunfang Zhao; Guanghao Song; Chunhua Fu; Yanshan Dong; Hang Xu; Hua Zhang; Long Jiang Yu (Plant Cell Reports, 2016)

MicroRNA let-7g cooperates with interferon/ribavirin to repress hepatitis C virus replication - Wen-Wen Chou; Chung-Feng Huang; Ming-Lun Yeh; Yi-Shan Tsai; Ming-Yen Hsieh; Ching-I Huang; Jee-Fu Huang; Pei-Chien Tsai; Edward Hsi; Suh-Hang Hank Juo; Wei-Lun Tsai; Wan-Long Chuang; et al. (Journal of Molecular Medicine, 2016)

Combination of retinoic acid, dimethyl sulfoxide and 5-azacytidine promotes cardiac differentiation of human fetal liver-derived mesenchymal stem cells - Fuxue Deng; Han Lei; Yunfeng Hu; Linjing He; Hang Fu; Rui Feng; Panpan Feng; Wei Huang; Xi Wang; Jing Chang (Cell and Tissue Banking, 2016)

Prauserella endophytica sp. nov., an endophytic actinobacterium isolated from Tamarix taklamakanensis - Jia-Meng Liu; Xugela Habden; Lin Guo; Li Tuo; Zhong-Ke Jiang; Shao-Wei Liu; Xian-Fu Liu; Li Chen; Rong-Feng Li; Yu-Qin Zhang; Cheng-Hang Sun (Antonie van Leeuwenhoek, 2015)

l-Amino acid carbamate prodrugs of scutellarin: synthesis, physiochemical property, Caco-2 cell permeability, and in vitro anti-oxidative activity - Yu-Feng Cha; Shun Zhang; Hang Su; Yu Ou; Xiao-Zhong Fu; Feng-Jie Jiang; Yong-Long Zhao; Yong-Xi Dong; Min Luo; Yong Huang; Yan-Yu Lan; Ai-Min Wang; et al. (Medicinal Chemistry Research, 2015)

Effects of rosuvastatin on the production and activation of matrix metalloproteinase-2 and migration of cultured rat vascular smooth muscle cells induced by homocysteine - Ya-fei Shi; Ju-fang Chi; Wei-liang Tang; Fu-kang Xu; Long-bin Liu; Zheng Ji; Hai-tao Lv; Hang-yuan Guo (Journal of Zhejiang University-SCIENCE B, 2013)

The cell-specific upregulation of bone morphogenetic protein-10 (BMP-10) in a model of rat cortical brain injury - Yaohua Yan; Peipei Gong; Wei Jin; Jian Xu; Xiaohong Wu; Ting Xu; Qinglei Hang; Hongran Fu; Kaifu Kei; Yilu Gao (Journal of Molecular Histology, 2012)

A Novel Method for Automatic Identification of Motion Artifact Beats in ECG Recordings - Yuewen Tu; Xiuquan Fu; Dingli Li; Chao Huang; Yawei Tang; Shuming Ye; Hang Chen (Annals of Biomedical Engineering, 2012)

Isolation and characterization of an antimicrobial peptide from bovine hemoglobin α-subunit - Jianhe Hu; Minglu Xu; Bolin Hang; Lan Wang; Qing Wang; Junjie Chen; Tao Song; Dengfeng Fu; Ziliang Wang; Sanhu Wang; Xingyou Liu (World Journal of Microbiology and Biotechnology, 2011)

MoFLP1, encoding a novel fungal fasciclin-like protein, is involved in conidiation and pathogenicity in Magnaporthe oryzae - Tong-bao Liu; Guo-qing Chen; Hang Min; Fu-cheng Lin (Journal of Zhejiang University-SCIENCE B, 2009)

A simple and effective method for total RNA isolation of appressoria in Magnaporthe oryzae - Tong-bao Liu; Jian-ping Lu; Xiao-hong Liu; Hang Min; Fu-cheng Lin (Journal of Zhejiang University-SCIENCE B, 2008)

Magnaporthe oryzae MTP1 gene encodes a type III transmembrane protein involved in conidiation and conidial germination - Qin Lu; Jian-ping Lu; Xiao-dong Li; Xiao-hong Liu; Hang Min; Fu-cheng Lin (Journal of Zhejiang University-SCIENCE B, 2008)

Silver nanoparticles: partial oxidation and antibacterial activities - Chun-Nam Lok; Chi-Ming Ho; Rong Chen; Qing-Yu He; Wing-Yiu Yu; Hongzhe Sun; Paul Kwong-Hang Tam; Jen-Fu Chiu; Chi-Ming Che (JBIC Journal of Biological Inorganic Chemistry, 2007)

A heavy sea fog event over the Yellow Sea in March 2005: Analysis and numerical modeling - Shanhong Gao; Hang Lin; Biao Shen; Gang Fu (Advances in Atmospheric Sciences, 2007)

Promoter trapping in Magnaporthe grisea - Xiao-hong Liu; Jian-ping Lu; Jiao-yu Wang; Hang Min; Fu-cheng Lin (Journal of Zhejiang University-SCIENCE B, 2006)